Estudo da qualidade da água distribuída pelo poço artesiano da FEG em relação à água servida pelo abastecimento público de Guaratinguetá - Barbosa, Priscila Marotti [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
We conducted a study of the quality of water distributed by Artesian Well in relation to water supply served by the public for purposes of human consumption of UNESP Campus Guaratinguetá. Two sections of the network were randomly chosen and monitored for 105 days: the stretch of the pipeline started off the Water Treatment Station of the Autonomous Service of Water, Sewage and waste in the Municipality of Guaratinguetá and ended in a point consumption of the Child Family Center, while the section B began at the output of an artesian well and finished in a point of consumption of the Department of Civil Engineering. It is the deterioration of water quality in parts A and B, through comparative analysis of Bicarbonates, Total Hardness, Total Iron, free residual chlorine, pH, Total Residual, Turbidity, Conductivity, Color, Fecal Coliforms and Total Coliforms. Among the observations that can be highlighted: the Total Hardness was found in highest concentration in the extract; for Total Iron significant variations were obtained for both parts, and reduction of this parameter in two points of consumption analyzed, not the expected increase concentration, because the contact of water along the pipe, the CRL showed significant depletion to section A, which can be related to impurities in the water, the presence of biofilm on the walls of pipes, or because this is the stretch of greater extent to be covered by water for pH, this indicated that the water is alkaline and slightly acidic stretch in section B; Turbidity was found for the higher concentration to the passage, and a considerable reduction of this parameter at point consumption due to deposition of particulate matter along the stretch, the conductivity also showed a higher concentration in the extract, as well as an increase in this parameter at the point of consumption. Upon leaving ... (Complete abstract click electronic access below)

Foi realizado um estudo da qualidade das águas distribuídas pelo Poço Artesiano em relação à água servida pelo Abastecimento Público, para fins de consumo humano do Campus da UNESP de Guaratinguetá. Dois trechos da rede foram escolhidos aleatoriamente e monitorados durante 105 dias: o trecho da canalização A iniciou-se na saída da Estação de Tratamento de Água do Serviço Autônomo de Água, Esgoto e Resíduo do Município de Guaratinguetá e finalizou-se em um ponto de consumo do Centro de Convivência Infantil da Faculdade de Engenharia, enquanto que, o trecho B iniciou-se na saída do Poço Artesiano e finalizou-se num ponto de consumo do Departamento de Engenharia Civil. Verificou-se a deterioração da qualidade das águas nos trechos A e B, através de análises comparativas de Bicarbonatos, Dureza Total, Ferro Total, Cloro Residual Livre, pH, Resíduo Total, Turbidez, Condutividade, Cor, Coliformes Fecais e Coliformes Totais. Dentre as observações que podem ser destacadas: a Dureza Total foi encontrada em maior concentração no trecho A; para o Ferro Total foram obtidas variações significativas para ambos os trechos, e redução deste parâmetro nos dois pontos de consumos analisados, e não o aumento esperado da concentração, devido o contato da água ao longo da tubulação; o CRL apresentou uma depleção significativa para o trecho A, o qual pode estar relacionado com as impurezas presentes na água, presença de biofilme nas paredes das tubulações, ou por este ser o trecho de maior extensão a ser percorrido pela água; para o pH, este indicou que a água é alcalina no trecho A e ligeiramente ácida no trecho B; para a Turbidez foi encontrada a concentração maior para o trecho A, e uma redução considerável deste parâmetro no ponto de consumo, devido à deposição das partículas em suspensão ao ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Água - Qualidade; Poços artesianos; Guaratinguetá - Abastecimento de água; Agua - Estações de tratamento; Deterioration of Water Quality